2018
DOI: 10.1038/s41598-018-21651-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Best1 Expression and Impaired Phagocytosis in an iPSC Model of Autosomal Recessive Bestrophinopathy

Abstract: Autosomal recessive bestrophinopathy (ARB) is caused by mutations in the gene BEST1 which encodes bestrophin 1 (Best1), an anion channel expressed in retinal pigment epithelial (RPE) cells. It has been hypothesized that ARB represents the human null phenotype for BEST1 and that this occurs due to nonsense mediated decay (NMD). To test this hypothesis, we generated induced pluripotent stem cells (iPSCs) from a patient with ARB and her parents. After differentiation to retinal pigment epithelial (iPSC-RPE) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…This result is in accordance with the localization of all mutations at the N‐terminal half of bestrophin‐1 whereas domains for β‐subunit binding are on the C‐terminus. Comparable to other expression systems, in CHO‐K1, mutant bestrophin‐1 showed reduced surface expression. The Ca V 1.3 interaction reduces Ca V 1.3 plasma membrane localization as well.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This result is in accordance with the localization of all mutations at the N‐terminal half of bestrophin‐1 whereas domains for β‐subunit binding are on the C‐terminus. Comparable to other expression systems, in CHO‐K1, mutant bestrophin‐1 showed reduced surface expression. The Ca V 1.3 interaction reduces Ca V 1.3 plasma membrane localization as well.…”
Section: Discussionmentioning
confidence: 64%
“…Studies of mutant bestrophin‐1 in heterologous expression reported data representative for absence of WT‐bestrophin‐1 . Studies using iPSC‐generated RPE cells from patients with BVMD report slightly different results showing that the presence of WT‐bestrophin‐1 influences the outcome . The patients` iPSC model, however, does not permit differential detection of mutant versus WT‐bestrophin‐1 and bears the disadvantage that different cell lines from the same iPSC show strong variances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wound healing response has provided the basis, for example, for the use of platelet lysates in MSC cell culture . We too have observed that platelet lysate is an excellent replacement for serum in the growth of cells differentiated from iPSCs . For these reasons, the use of other components of the wound healing response such as fibrinogen/fibrin seems logical.…”
Section: Discussionmentioning
confidence: 99%
“…The previously described iPSC line 006‐BIOTR‐0001, obtained from fibroblasts and reprogrammed with Sendai virus kit (Thermo Fisher, Waltham, MA; clone 1, Mayo Clinic) was used for all experiments . Additional lines used to validate reproducibility of the fibrinogen coating included the previously described IMR‐90‐4, obtained from a immortalized human fibroblast cell line and reprogrammed using lentiviral vectors (clone 4; WiCell; Madison, WI), and a new line, 018‐BIOTR‐0089 (clone 18), produced by reprogramming of human peripheral blood lymphocytes using episomal DNA transfection. mTESR (Stem Cell Technologies, Vancouver, BC, Canada) was used for iPSC growth, and ReLeSR (Stem Cell Technologies) was used to dissociate cells for passage.…”
Section: Methodsmentioning
confidence: 99%